Entrance to the Garbhagriha decorated with an ornate Dvarashakha - Temples of India Project Team (Jio Institute, 2024)
The entrance to the garbhagriha (sanctum sanctorum) is decorated with an ornate dvarashakha (architrave or vertical band). It consists of panchashakhas, meaning five vertical divisions on either side of the dvarashakha. The threshold at the centre bottom is decorated with floral motifs. Above the lintel beam is a row of miniature niches, called rathikas that have engravings of divinities. All the vertical divisions of the dvarashakha have figures carved. These consist of depictions of river Goddesses, apsaras (celestial damsels) and Shaiva attendants. The attendants are carved on the most protruding shakha called the stambha shakha. The lalatabimba (centre of the lintel) has an image of Lakulisa, indicating that the temple was affiliated with the Pashupata Shaiva tradition.